Reformulasi Hukum KIK: Menyeimbangkan Kepentingan Kolektif dan Individual dalam Perlindungan Hukum Tenun Cual Bangka Belitung - Marlinda Marlinda; Syafri Hariansah (Jurnal Ilmiah Kebijakan Hukum, 2025)
The designation of Cual Weaving as Bangka Belitung Communal Intellectual Property raises legal and social problems, especially regarding the tension between collective protection and the individual rights of craftsmen. Craftsmen feel that KIK status reduces recognition of individual contributions and marketing creativity of Cual Weaving. Public perception regarding the prohibition on the use of terms “Tenun Cual” outside the craftsman group adds to the complexity of this issue. This research aims to analyze the juridical aspects to answer the question of what is the ideal legal construction in balancing communal protection and individual rights in the Tenun Cual case. Normative juridical research methods use secondary data and literature studies. This research identifies regulatory gaps in Government Regulation No. 56 of 2022 concerning KIK and Law No. 28 of 2014 concerning Copyright which does not yet accommodate the rights of individual craftsmen in a communal system, and formulate innovative legal protection models that balance the collective and the individual. Offers a layered system protection model, combining collective and individual protection with a licensing mechanism through the community and recognition of craftsmen’s innovation. The main focus is to develop legal mechanisms that can bridge the interests of cultural preservation and the fulfillment of the economic and creative rights of craftsmen. The research results show that the existing legal framework has not been able to balance communal protection with recognition of individual contributions. For this reason, a more inclusive legal reconstruction is needed to guarantee communal protection without ignoring individual economic and innovation rights, as well as recommending the formation of regulations, including regulation of use rights and community-based licensing models, in order to maintaining a balance between cultural preservation and the interests of craftsmen. An adaptive legal approach is needed so that Cual Weaving is protected as cultural heritage, but also becomes a source of prosperity through parallel and model protection mechanisms benefit-sharing which is fair. adaptive legal approach is needed so that Cual Weaving is protected as cultural heritage, but also becomes a source of prosperity through parallel and model protection mechanisms benefit- sharing which is fair.